Community law and supra-nationality in regional integration : the role of regional tribunals - Anderson, Winston (2013)
Argues for some form of supra-nationality of Community law, stating that one of the greatest challenges to the regional integration process, is insinuating and making pre-eminent Community law in the national legal systems of Member States.